The Effectiveness of the BAHAGIA Package on the Subjective Well-Being of Post-Stroke Patients - Melsandi Melsandi; M Sobirin Mohtar; Asmadiannor Asmadiannor (JENDELA NURSING JOURNAL, 2023)
Background: stroke can leave symptoms or further impacts in all aspects of life such as loss of doing activities and changing roles. Changes that occur in post-stroke patients need to be given home care therapy, one of which is using the "BAHAGIA" Package which consists of a series of words BINGAH, AYEM, HANDOKO, ABIYASA, GALIH, IGUH, and APIK.Purpose: to determine the effectiveness of the BAHAGIA Package on the Subjective Well-Being of post-stroke patients in the Cempaka Putih Public Health Center, Banjarmasin.Methods: this study used quantitative research with Pre-Experimental pre-post test design and purposive sampling technique, totaling 30 people. The data collection instrument used a questionnaire.Results: based on research results from Subjective Well-Being respondents in the medium category as many as 2 people (7%) and high as many as 28 people (93%). The results of the Wilcoxon test obtained a significance value of 0.000 0.05 indicating that there is an effectiveness of the BAHAGIA Package on the Subjective Well-Being of post-stroke patients.Conclusion: based on the results of the study, it can be concluded that there is an effectiveness of the BAHAGIA Package on the Subjective Well-Being of post-stroke patients in the Work Area.